Pemanfaatan Media Google Classroom pada Pembelajaran Fiqih di Masa Pandemi Covid 19 - Atiqatul Musyarofah; Mega Irmawati; Kholilur Rahman (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
Along with the development of technology and communication, during the Covid 19 pandemic, learning is carried out online. On the one hand, online learning has received appreciation from the community. On the other hand, a problem arises, where the learning substance is not absorbed properly. This study aims to analyze the use of google classroom media during the covid-19 pandemic in learning fiqh at SMAN Darussholah Singojuruh Banyuwangi for the 2020/2021 academic year. This study uses a descriptive qualitative approach. The results showed that the fiqh teacher at SMAN Darussholah had prepared learning tools such as lesson plans and syllabus before learning. In addition, the teacher created a google classroom, prepared learning materials and various tools for learning. Meanwhile, students read and understand the material, discuss together about the material discussed, and answer questions/questions that have been given by the teacher. In the evaluation, the teacher conducted a written test and made a video. So that learning is more optimal, the teacher must be professional, the appearance of the google classroom media is attractive, can be accessed anywhere. At the same time, there must be good communication between institutions and teachers and parents. This is intended so that there is continuity of fiqh learning outside school hours.